Small airway inflammation and extrafine inhaled corticosteroids plus long-acting beta2-agonists formulations in chronic obstructive pulmonary disease. (October 2018) - Pirina, Pietro; Foschino Barbaro, Maria Pia; Paleari, Davide; Spanevello, Antonio
Abstract: Objectives: To summarize the evidence of small airways involvement in chronic obstructive pulmonary disease (COPD) pathophysiology, and to evaluate the efficacy of extrafine formulations of inhaled corticosteroids (ICS) in combination with long-acting beta2 -agonists (LABAs) in the treatment of COPD. Data source: A search of the PubMed database was conducted using the keywords "COPD", "small airways", "inflammation" and "extrafine formulation." The search was limited to entries published in English before August 2016. Only studies conducted in humans were considered. Study selection: Publications were included on the basis of relevance. Results: COPD is a common preventable and treatable disease, characterized by persistent and progressive airflow limitation. With improved understanding of COPD pathophysiology, small airways (internal diameter <2 mm), a well-known major site of COPD-associated inflammation and remodeling, have emerged as a potential target for COPD pharmacologic therapies. The ability of extrafine formulations of ICS in combination with LABAs to achieve central and peripheral lung deposition, and the implications of the enhanced efficacy that this may bring, are discussed by examining findings from the development trials plan of the extrafine formulation of beclometasone dipropionate/formoterol fumarate (Foster ®, Chiesi Farmaceutici, Italy) in patients with COPD. Conclusion: There is an urgent need for improved and reliable techniques for small airways assessment in order to detect early damage, disease progression and response to treatment. Evidence from randomized clinical trials supports the benefits of extrafine ICS/LABA formulations in COPD, real world studies are necessary to confirm this. Highlights: Small airway inflammation is feature of chronic obstructive pulmonary disease. Small airway structural abnormalities lead to progressive airflow limitation. Inhaled corticosteroids plus long-acting beta2 agonists provide clinical benefits. Extrafine formulations can reach and treat the principle site of inflammation.